Os Bancos Centrais e sua ambivalência público-privada [Central Banks and their public-private nature] - Gentil Corazza (Nova Economia, 2001)
The paper analyzes the historic origin of Central Banks, from three basic processes: the evolution and convergence of the free banking system to a hierarchical and centralized system in the Central Bank; the transformation of Clearing Houses in Central Banks, and finally, the processes by which governmental banks were assuming Central Banks functions and transforming themselves in Central Banks. The assumes the hypothesis by which the Central Banks were not created arbitrarily by Government, but from the evolution of private banking system suffering periodic crises, which needed public intervention. Finally, the paper concludes that this historic origin grounds the ambivalent public-private nature in Central Banks.